Human Resource Management and Ethics at Work - Grover, Lisa (Routledge, 2025)
Human Resource Management and Ethics at Work dives deep into understanding ethical human resources practice, including professional codes of conduct and what it means to be an ethical human resources professional. Each chapter explores the philosophical underpinnings of the ethical challenges faced by contemporary human resources professionals. It draws upon narratives from fiction and film to bring these scenarios to life.Each chapter utilises theories and concepts from philosophy to equip current and aspiring human resources professionals to think about ethical issues. There are no right answers here, but by provoking debate and discussion, human resources professionals can make better choices. Through understanding and practice, we become ethical human resources professionals. The book is structured around the three ethical perspectives. First, the perspective of the individual human resources professional, focusing on good character and the traits of an ethical human resources professional. Second, the relationship between the individual human resources professional, the organisation and its employees, and human resources professional bodies. The human resources professional aims to have a positive impact on working lives but has to navigate a complex network of relationships and responsibilities. Third, the narrative moves to the macro level, identifying the social responsibilities of the human resources professional beyond their own organisation. A section of the book is dedicated to each of these pillars, exploring what they mean for the practising HR professional. Concepts and theories from philosophy are applied to understand this meaning. These tools can then be applied to novel situations that HR professionals go on to encounter in the workplace. Teaching activities are included throughout the book.This is an ideal resource for those undertaking an undergraduate or postgraduate course in human resource management, practising human resources professionals who worry about the right thing to do, or anyone interested in people management ethics.